The Impact of Marriage on Early Childhood Behavior Based on a Positive Legal Perspective - Amalia, Hilda Vivi; Putra, Budayawan Gerio; Pratama, Rafi; Aulia, Rd. I Ilham Maulana; Maharani, Rimayyasa Agustin (Journal of Current Research In Multidisciplinary, 2024)
This study aims to increase knowledge about the impact of marriage on early childhood from a positive legal perspective for students of SMA PGRI 22 Serpong. This community service activity targets the students of SMA PGRI 22 Sepong, which is located at Jl. Pahlawan Seribu, Cilenggang, Kec. Serpong, South Tangerang City, Banten. Students from the Faculty of Law at Pamulang University, who conducted PKM, provided the independent funds for this activity. Students from SMA PGRI 22 Serpong, located at Jl. Pahlawan Seribu, Cilenggang, Kec. Serpong, South Tangerang City, Banten, attended this activity on May 16, 2024. The success of this community service activity was largely due to the support from various parties, particularly the enthusiastic and active participation of the participants. Therefore, we should expand the scope of this socialization activity in the future, and expand the scope of the presented material to enhance the participants' knowledge and comprehension.